# Solve for t 1 9/18*(lessth)=3 7/9 1918⋅(les⋅sth)=379
Simplify 1918⋅(les⋅sth).
Convert 1918 to an improper fraction.
A mixed number is an addition of its whole and fractional parts.
(1+918)⋅(les⋅sth)=379
Add 1 and 918.
Write 1 as a fraction with a common denominator.
(1818+918)⋅(les⋅sth)=379
Combine the numerators over the common denominator.
18+918⋅(les⋅sth)=379
Add 18 and 9.
2718⋅(les⋅sth)=379
2718⋅(les⋅sth)=379
2718⋅(les⋅sth)=379
Multiply s by s by adding the exponents.
Move s.
2718⋅(le(s⋅s)th)=379
Multiply s by s.
2718⋅(les2th)=379
2718⋅(les2th)=379
Cancel the common factor of 27 and 18.
Factor 9 out of 27.
9(3)18⋅(les2th)=379
Cancel the common factors.
Factor 9 out of 18.
9⋅39⋅2⋅(les2th)=379
Cancel the common factor.
9⋅39⋅2⋅(les2th)=379
Rewrite the expression.
32⋅(les2th)=379
32⋅(les2th)=379
32⋅(les2th)=379
Multiply 32(les2th).
Combine l and 32.
l⋅32(es2th)=379
Combine e and l⋅32.
e(l⋅3)2(s2th)=379
Combine s2 and e(l⋅3)2.
s2(e(l⋅3))2(th)=379
Combine t and s2(e(l⋅3))2.
t(s2(e(l⋅3)))2h=379
Combine t(s2(e(l⋅3)))2 and h.
t(s2(e(l⋅3)))h2=379
t(s2(e(l⋅3)))h2=379
Move 3 to the left of ts2el.
3ts2elh2=379
3ts2elh2=379
Convert 379 to an improper fraction.
A mixed number is an addition of its whole and fractional parts.
3ts2elh2=3+79
Add 3 and 79.
To write 3 as a fraction with a common denominator, multiply by 99.
3ts2elh2=3⋅99+79
Combine 3 and 99.
3ts2elh2=3⋅99+79
Combine the numerators over the common denominator.
3ts2elh2=3⋅9+79
Simplify the numerator.
Multiply 3 by 9.
3ts2elh2=27+79
Add 27 and 7.
3ts2elh2=349
3ts2elh2=349
3ts2elh2=349
3ts2elh2=349
Multiply both sides of the equation by 13(e2).
13(e2)⋅3ts2elh2=13(e2)⋅349
Simplify both sides of the equation.
Simplify 13(e2)⋅3ts2elh2.
Combine 3 and e2.
13e2⋅3ts2elh2=13(e2)⋅349
Multiply the numerator by the reciprocal of the denominator.
123e⋅3ts2elh2=13(e2)⋅349
Multiply 23e by 1.
23e⋅3ts2elh2=13(e2)⋅349
Cancel the common factor of 2.
Cancel the common factor.
23e⋅3ts2elh2=13(e2)⋅349
Rewrite the expression.
13e⋅(3ts2elh)=13(e2)⋅349
13e⋅(3ts2elh)=13(e2)⋅349
Cancel the common factor of 3e.
Factor 3e out of 3ts2elh.
13e⋅(3e(ts2lh))=13(e2)⋅349
Cancel the common factor.
13e⋅(3e(ts2lh))=13(e2)⋅349
Rewrite the expression.
ts2lh=13(e2)⋅349
ts2lh=13(e2)⋅349
ts2lh=13(e2)⋅349
Simplify 13(e2)⋅349.
Combine 3 and e2.
ts2lh=13e2⋅349
Multiply the numerator by the reciprocal of the denominator.
ts2lh=123e⋅349
Multiply 23e by 1.
ts2lh=23e⋅349
Multiply 23e⋅349.
Multiply 23e and 349.
ts2lh=2⋅343e⋅9
Multiply 2 by 34.
ts2lh=683e⋅9
Multiply 9 by 3.
ts2lh=6827e
ts2lh=6827e
ts2lh=6827e
ts2lh=6827e
Divide each term by s2lh and simplify.
Divide each term in ts2lh=6827e by s2lh.
ts2lhs2lh=6827e⋅1s2lh
Simplify ts2lhs2lh.
Cancel the common factor of s2.
Cancel the common factor.
ts2lhs2lh=6827e⋅1s2lh
Rewrite the expression.
tlhlh=6827e⋅1s2lh
tlhlh=6827e⋅1s2lh
Cancel the common factor of l.
Cancel the common factor.
tlhlh=6827e⋅1s2lh
Rewrite the expression.
thh=6827e⋅1s2lh
thh=6827e⋅1s2lh
Cancel the common factor of h.
Cancel the common factor.
thh=6827e⋅1s2lh
Divide t by 1.
t=6827e⋅1s2lh
t=6827e⋅1s2lh
t=6827e⋅1s2lh
Multiply 6827e and 1s2lh.
t=6827es2lh
t=6827es2lh
Solve for t 1 9/18*(lessth)=3 7/9

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top